Spatial dimensions of dichotomous adaptive responses to natural hazards in coastal districts of West Bengal, India. (September 2021) - Bera, Subhas; Das, Arup; Mazumder, Taraknath
Abstract: Developing countries continue to reel under the impact of hydro meteorological disasters which have been aggravated by climate change. Communities exposed to such vagaries of nature continuously strive to adapt to such events. These adaptive practices can be traced spatially through transformations in Land Use Land Cover (LULC). This study hypothesizes that these spatial transformations are a function of the spatial manifestation due to changes in livelihood practices resulting from exposure to natural hazards. Moreover, the spatial dimensions of changes observed are dichotomous in nature and express themselves differently based on local stimuli. LULC transformations between the period 2002–2014, along with socio-economic data and semi-structured interviews were used to identify the drivers of LULC changes in coastal districts of West Bengal, India. In this study, evidence of transformations triggered by natural hazards are differently expressed for zone in proximity to coastal areas and zone in proximity to a primate metropolitan area. Results from the analyses show three predominant changes - increasing trends from agriculture to aquaculture practices in coastal tidal influence Blocks (270.39%), trends of rapid urbanization, and increases of the built-up (rural) area in Blocks adjoining the metropolitan area (58.18%). Statistical analyses revealed that the changes in the area under aquaculture can be attributed to change in area under agriculture practice and accessibility to a station of suburban railway network. Similarly, for Blocks in the rural areas, it was observed that the change in the built-up area can be explained by existing built-up area/fallow land and its distance from the district headquarter. Graphical Abstract: ga1 Highlights: Assessment of adaptive practices from recurrent exposure to natural hazards. Responses are prevalently related to livelihood and economic opportunities. Responses are measured through spatiotemporal changes in LULC. Transition from agriculture to aquaculture in coastal tidal influenced area. Changes from agriculture to fallow to built-up area in adjoining the metropolitan region.